Assessment of hydrogen quality dispensed for hydrogen refuelling stations in Europe. (18th August 2021) - Aarhaug, Thor Anders; Kjos, Ole; Bacquart, Thomas; Valter, Vladimir; Optenhostert, Thomas
Abstract: The fuel quality of hydrogen dispensed from 10 refuelling stations in Europe was assessed. Representative sampling was conducted from the nozzle by use of a sampling adapter allowing to bleed sample gas in parallel while refuelling an FCEV. Samples were split off and distributed to four laboratories for analysis in accordance with ISO 14687 and SAE J2719. The results indicated some inconsistencies between the laboratories but were still conclusive. The fuel quality was generally good. Elevated nitrogen concentrations were detected in two samples but not in violation with the new 300 μmol/mol tolerance limit. Four samples showed water concentrations higher than the 5 μmol/mol tolerance limit estimated by at least one laboratory. The results were ambiguous: none of the four samples showed all laboratories in agreement with the violation. One laboratory reported an elevated oxygen concentration that was not corroborated by the other two laboratories and thus considered an outlier. Highlights: 10 samples collected from nozzle of public HRS in Europe. Standardized sampling methodology applied. All samples analysed by four laboratories = 40 analyses. Extensive evaluation of interlaboratory results. Discrepancies in H2 fuel violation depending on laboratory.